2017
DOI: 10.1097/mib.0000000000001099
|View full text |Cite
|
Sign up to set email alerts
|

Management of Inflammatory Bowel Disease in the Elderly Patient

Abstract: The population of older patients with inflammatory bowel disease (IBD) continues to grow, partly reflecting the aging global population in general. The debilitating effects of IBD compound age-related decrements in health and functional capacity, and make the medical management of older patients with Crohn’s disease and ulcerative colitis distinctly challenging to clinicians. Here, we review the recent literature describing the pharmacologic management of IBD in this population, with focus on the safety, toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 122 publications
(170 reference statements)
3
64
1
Order By: Relevance
“…However, such immunosuppression may be associated with rare but serious adverse effects including infections and treatment‐related cancers. One population that is particularly vulnerable to such adverse effects but is frequently excluded from clinical trials and observational cohorts is the older IBD patient …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such immunosuppression may be associated with rare but serious adverse effects including infections and treatment‐related cancers. One population that is particularly vulnerable to such adverse effects but is frequently excluded from clinical trials and observational cohorts is the older IBD patient …”
Section: Introductionmentioning
confidence: 99%
“…Up to one‐fifth of patients with IBD may be diagnosed after the age of 60 years . Owing to the ageing of the population, patients older than age 60 years represent a growing subgroup of those with IBD globally . Studies have demonstrated that IBD in older patients is associated with significant morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…1 Managing older IBD patients poses unique challenges for clinicians, who must balance the benefits of chronic immunosuppression with a higher burden of patient comorbidity and risks of treatment-and disease-related adverse events (AEs). 2 Asscher et al recently reported results from the prospective Dutch Initiative on Crohn's Colitis (ICC), comparing the effect of comorbidity and age on impaired safety outcomes in IBD patients treated with second generation biologics. 3 Among 203 vedolizumab-and 207 ustekinumab-exposed patients, comorbidity burden was independently associated with negative safety outcomes, particularly hospitalisations, whereas age was not.…”
Section: N V I T E D E D I T O R I a L Editorial: Is Age Just A Nummentioning
confidence: 99%
“…Approximately 10%‐30% patients with IBD are older than 60 years, and with an aging population and chronic nature of IBD, the prevalence of IBD in older adults is anticipated to continuously rise . Based on the 2015 National Health Interview Survey, an estimated 1.7% adults ≥65 years (approximately 805 000) reported a diagnosis of IBD .…”
Section: Introductionmentioning
confidence: 99%